2002
DOI: 10.1039/b201700h
|View full text |Cite
|
Sign up to set email alerts
|

A chip-based capillary electrophoresis-contactless conductivity microsystem for fast measurements of low-explosive ionic components

Abstract: A miniaturized analytical system for separating and detecting inorganic explosive residues, based on the coupling of a micromachined capillary electrophoresis (CE) chip with a contactless conductivity detector is described. The low electroosmotic flow (EOF) of the poly(methylmethacrylate) (PMMA) chip material facilitates the rapid switching between analyses of cations and anions using the same microchannel and run buffer (and without an EOF modifier), and hence offers rapid ( < 1 min) measurement of seven expl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
83
0

Year Published

2002
2002
2020
2020

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 96 publications
(90 citation statements)
references
References 19 publications
6
83
0
Order By: Relevance
“…Fast-and slow-migrating anions were separated in less than 90 seconds [84] and a fast separation of inorganic anions within 15 seconds [94] was demonstrated in PMMA chips. Four alkylated methylphosphonic acids, characterized as degradation products of chemical warfare agents, were separated in PMMA microchips in the anionic separation mode by Wang et al [96].…”
Section: Contactless Conductivity Detection In Microchip Electrophoresismentioning
confidence: 97%
See 2 more Smart Citations
“…Fast-and slow-migrating anions were separated in less than 90 seconds [84] and a fast separation of inorganic anions within 15 seconds [94] was demonstrated in PMMA chips. Four alkylated methylphosphonic acids, characterized as degradation products of chemical warfare agents, were separated in PMMA microchips in the anionic separation mode by Wang et al [96].…”
Section: Contactless Conductivity Detection In Microchip Electrophoresismentioning
confidence: 97%
“…Several authors have demonstrated the application of devices with embedded insulated electrodes to the determination of inorganic cations [80,83,92,93]. Wang and co-workers [84,94] and Tanyanyiwa et al [35,85] demonstrated the determination of inorganic cations in glass and PMMA devices. Limits of detection of about 1 mM were reported for the determination of inorganic cations when using elevated voltages for detection [35].…”
Section: Contactless Conductivity Detection In Microchip Electrophoresismentioning
confidence: 98%
See 1 more Smart Citation
“…The electrode pairs are screenprinted and cut into cover sheets and subsequently sealed onto channel plates thus creating an integrated separation and detection device. Such screen-printed detectors do not require manual fabrication of the electrodes from metal foils [5,15] or other tedious protocols [8, 12 -14]. The new scheme enables fast fabrication and alignment of the sensing electrodes with the channel plate and thus dramatically decreases the overall analytical device fabrication time.…”
Section: Introductionmentioning
confidence: 98%
“…Various electrode materials such as silver paint [10], platinum [8,12], platinum-iridium [13], gold [14], copper [15], and aluminum [5,6] have been used as conductivity (both contact and contactless) detector electrodes and the fabrication process has usually involved various methods ranging from sputtering of the metal [6,8,12], physical placement of the electrode close to the separation channel [7], electron beam evaporator [14], or gluing either copper [15] or aluminum layers [5] onto the cover plate. While the photolithographic methods are difficult to carry out, other normal deposition methods such as sputtering and thermal or electron beam evaporation require etching steps and hence impose limitations in dimensions of the electrodes.…”
Section: Introductionmentioning
confidence: 99%